Sosialisasi Penemuan dan Pemasyarakatan Olahraga Rekreatif “Pancoair” dalam Rangka Meningkatkan Industri Wisata Air - Syahri Alhusin; Shodiq Hutmono (Jurnal Abdimas Adpi Sosial dan Humaniora, 2022)
Since the discovery of the Pancoair recreational sports design, quite a number of program activities have been carried out to develop and promote Pancoair. Among them are obtaining the Uberhaki Program from the Director General of Higher Education in 2001 to propose a Pancoair Patent, obtaining a MURI certificate in 2002, obtaining the Student Alternative Work Program in 2003, which was used to promote Pancoair throughout the districts of the former Surakarta Residency. In 2008 we held Pancoair performances and socialization in several swimming pools, including: at the Manahan Solo swimming pool, the Pengging Boyolali swimming pool, the Kartasuro Kopasus swimming pool, the Jolotundo Klaten swimming pool, and the Karanganyar swimming pool. In 2012, there were 300 Pancoair Seminars and Shows conducted by POK UTP students. In 2016-2019 the sport of Pancoair has been placed in the Muslim Oubond "Istiqlal Outbind" at the Sujono Taruno Foundation Orphanage. Where children who play oubond also play Pancoair.Given the enthusiasm of the community with the sport of pancoair, the planned future activities include: Will cooperate with the industry to produce Pancoair Pedestals. Will collaborate with Tourism Offices throughout Indonesia to hold Pancoair Recreational Sports in several swimming pools. Will cooperate with hotels that have swimming pools, which can be used for Pancoair recreational sports. Will make a special Pancoair swimming pool at the Tunas Pembangunan Solo Sports Center and invite and train sports teachers in playing the Pancoair sport.